Growth of Ge1−xSnx Nanowires by Chemical Vapor Deposition via Vapor–Liquid–Solid Mechanism Using GeH4 and SnCl4. Issue 1 (22nd November 2017) - Haffner, Thibault; Zeghouane, Mohammed; Bassani, Franck; Gentile, Pascal; Gassenq, Alban; Chouchane, Fares; Pauc, Nicolas; Martinez, Eugenie; Robin, Eric; David, Sylvain; Baron, Thierry; Salem, Bassem
Abstract : In this work we report on the elaboration and characterization of Ge1− x Sn x nanowires synthetized by chemical vapor deposition (CVD) via vapor–liquid–solid (VLS) mechanism using GeH4 and SnCl4 as precursors. We have investigated tin incorporation in Ge as a function of experimental growth conditions such as growth temperature and Sn precursor partial pressure ( P SnCl4 / P GeH4 ratio). We have demonstrated Ge1− x Sn x nanowires with Sn incorporation around 1 at.% in the core with a thin Sn‐rich shell with up to 10 at.% Sn well beyond the equilibrium solubility of Sn in bulk Ge. Abstract : The authors report on the characterization of GeSn nanowires grown by chemical vapor deposition via vapor–liquid–solid mechanism using GeH4 and SnCl4 as precursors. The incorporation of Sn and its spatial distribution in these nanowires were analyzed using Raman, nano‐Auger, and STEM‐EDX measurements highlighting a thin Sn‐rich shell with up to 10 at.% Sn.